Acarofauna of reptiles and amphibians of Brazil: Morphological and molecular studies and pathogens research - Roldan, Jairo Alfonso Mendoza (2019)
Brazil is a megadiverse country in herpetofauna, with 796 species of reptiles, and 1,080 species of amphibians. The high urbanization and the marked deforestation have increased the number of human-herpetofauna encounters. This fact has made some species to be considered currently as synanthropic. Reptiles and amphibians are known amplifiers and reservoirs of several pathogens, yet the role of these animals in the cycle of diseases and the vector potential of the ectoparasitic mites of these vertebrates are poorly known. These hosts are parasitized by more than 500 species of mites, distributed in 61 genera of 13 families that belong to the Trombidiformes (Acariformes), Mesostigmata and Ixodida (Parasitiformes) orders. In the Brazil context, the fragmentary records of species of mites of these orders, especially in the north and northeast regions, their taxonomic complexity and the scarce information regarding their role in the epidemiology of diseases, where the main reasons to pursue the proposition of the present study. Mites of reptiles and amphibians deposited in the Acari collection of the Instituto Butantan (IBSP) were reviewed and identified. Six other collections in various places where also visited (Argentina, Brazil, United States, France and Belgium). Also, mites collected at the animal reception site of the Instituto Butantan, and from field collections were also identified. Part of this material was prepared for molecular studies and phylogenetic inference using ribosomal and mitochondrial genes, and another part of the material was used to assess the presence of Borrelia spp., Coxiella spp., Hepatozoon spp. and Rickettsia spp. Of the subclass Acari, Six families, 12 genera and 32 species of Trombidiformes mites were identified, 23 occurring in Brazil, increasing six new species to the Brazilian territory. The Oribatid mite A. longisetosus was identified apparently parasitizing a frog, which is a new host-parasite association. Six families, 11 genera and 17 species of Mesostigmata mites were identified, wit 16 species occurring in Brazil, with one new species described (Chironobius n. sp.). Two families, four genera and 19 species of ticks were identified, 17 occurring in Brazil, with one new species of argasid tick registered in Brazil, with an argasid tick of the genus Ornithodoros (Alectorobius). The total number of Acari parasites of herpetofauna in Brazil after this study is 56 species. Many hosts are new records, as well as, some of the localities are new records of distribution. 4,515 reptiles and amphibians were examined, of which 170 were infested with mites and ticks. Assessing blood smears allowed to correlate hemoparasitic presence with ectoparasitic prevalence, and the histologic slides of amphibians helped better characterize the typical lesion produced by intradermic mites of the genus Hannemania. A phylogeny inference using the 18S V4 rRNA gene for Acari was proposed that inferred a polyphyletic Acari, with different bootstrap values for the monophyly of Acariformes and Parasitiformes. Hepatozoon was detected in mite ticks and hosts blood. The sequences generated matched three main species with host and geographical delimitations (Hepatozoon sp. BT-2016, Hepatozoon sp. CCS-2010 and Hepatozoon ayorgbor). Three species were identified for the gltA gene for Rickettsia, and four species were identified for the OmpA gene for the Spotted Fever Group Rickettsia from ixodid ticks, trombiculid, pterygosomatid, and Mesostigmata mites. None of the hosts tissue samples tested yielded positive. Rickettsia bellii in A. sculptum is a new report and the presence in a Eutrombicula alfreddugesi mite, is unprecedented. Rhickettisa rhipicephali was detected for the first time on Mesostigmata mites. Rickettisa amblyommatis was detected for the first time in A. rotundatum. The detection of R. aeschlimannii from a macronyssid mite (O. natricis), is unprecedented, and R. rickettsii in Pterygosomatidae mites is also a new report. The detection of SFG Rickettsia species on reptile mites (Mesostigmata and Pterygosomatidae) highlights the importance of an integrative assessment of ectoparasites of reptiles mainly due to the fragmentation of the habitat, which, consequently, prompts to a greater number of occurrences between humans, herpetofauna and acarofauna.